The dementia certified nurse process for acquiring knowledge for care of older adult patients with dementia in acute care hospitals: a qualitative descriptive study - Kabaya, Sonoko; Nagahata, Tayo; Juanamasta, I Gede (Universitas Airlangga, 2024)
Introduction: This study aimed to explore DCNs’ perceived knowledge acquisition in older adult patients with dementia in acute-care hospitals. Methods: The study used qualitative methods, with 14 Japanese DCNs involved in the snowball sampling method. Face-to-face interviews were conducted between June and December 2016 by the principal investigator. A qualitative content analysis was used in this study. The study results were divided into nine categories and 31 sub-categories. Results: This study highlights the process through which DCNs in acute-care hospitals acquire expertise in caring for older adults with dementia. Initially, DCNs faced dilemmas between patients’ resistance to treatment and their professional priorities, leading to emotional and cognitive shifts that motivated them to seek specialized knowledge and refine their care methods. By reflecting on their experiences, integrating patient-centered approaches, and sharing insights with team members, DCNs deepened their understanding, adapted care strategies, and enhanced their clinical capacity to meet patients' needs effectively. Conclusions: Nurses should provide appropriate training before taking care of the patients. Knowledge should be combined with patient’s problems and behavior. Thus, nurses become more flexible in adapting to patients with dementia. These findings emphasize the importance of fostering reflective practices and educational interventions to enhance DCNs’ expertise, enabling them to provide patient-centered care and improve outcomes for older adults with dementia.